DEFINING TERRITORIES IN AQUATIC PUBLIC SPACES: A CASE STUDY OF IJO MIGRANT FISHERMEN IN NIGERIA - Brisibe, Warebi G. (International Journal of Research -GRANTHAALAYAH, 2021)
This paper examines the issue of territoriality in aquatic public spaces and how it affects fishing rights amongst artisanal fishermen of Ijo ethnic origin, in the Niger Delta area of Nigeria. It focuses on how these fishermen view the concept of space and define territories with or without the play of architectural materiality and elements. The study adopts a qualitative approach using interviews, focus groups and oral history as methodologies. The findings show that although architecturally defined boundaries in form of markings or spatial demarcations are not common in the estuarine and riverine zones of the Niger Delta, they however exist. Often implied or expressed by actions indicative of territoriality, or even revealed through other anthropological symptoms.